2000
DOI: 10.1161/01.str.31.10.2437
|View full text |Cite|
|
Sign up to set email alerts
|

Symptomatic Ischemic Stroke in Full-Term Neonates

Abstract: Background and Purpose-The present multicenter case-control study was prospectively designed to assess the extent to which single and combined clotting factor abnormalities influence the onset of symptomatic ischemic stroke in full-term neonates. Methods-Lipoprotein (Lp)(a); the factor V (FV) G1691A mutation; the prothrombin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
2
5

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(75 citation statements)
references
References 48 publications
2
66
2
5
Order By: Relevance
“…20 The prevalence of MTHFR1298 mutation in our study was comparable to the wide range of incidence reported in the United States population. 33 Previous studies have reported an increased prevalence of FVL and MTHFR mutations in neonates and children with thrombosis compared to the general population 16,34 and have also shown an increased risk of catheter-related thrombosis in patients with FVL; 12,13 however, we found no difference in the prevalence of MTHFR mutations and FVL mutation in infants with and without thrombosis.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…20 The prevalence of MTHFR1298 mutation in our study was comparable to the wide range of incidence reported in the United States population. 33 Previous studies have reported an increased prevalence of FVL and MTHFR mutations in neonates and children with thrombosis compared to the general population 16,34 and have also shown an increased risk of catheter-related thrombosis in patients with FVL; 12,13 however, we found no difference in the prevalence of MTHFR mutations and FVL mutation in infants with and without thrombosis.…”
Section: Discussioncontrasting
confidence: 52%
“…12,13 Factor V Leiden (FVL) is the most commonly identified risk factor 14 and has been associated with an increased incidence of both spontaneous and catheter-associated thrombosis. 12,[15][16][17] The risk of spontaneous thrombosis increases eightfold in the heterozygous state, and 80-fold in the homozygous state. 18 Prevalence of heterozygous FVL in the North American Caucasian population is 4 to 6%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor V Leiden mutation, hyperhomocysteinemia, and elevated lipoprotein(a) levels all have been described with increased frequency in infants with PAS when compared with healthy control subjects. [25][26][27] Previous studies of PAS are subject to a number of important limitations. Most describe only a small number of children 6,7,10,15,24,28 or lack an adequate comparison group to assess the significance of potential risk factors.…”
mentioning
confidence: 99%
“…6,37 Other hematological disturbances associated with pediatric stroke include iron-deficiency anemia 11,38 and polycythemia. 39 In neonates, peripartum factors such as preeclampsia, prolonged rupture of membranes, and placental abnormalities are risks. 6,40 In older children, metabolic disorders may produce stroke or stroke-like episodes including MELAS, 41 Fabry disease, 42 and hyperhomocysteinemia.…”
Section: Risk Factors and Pathophysiologymentioning
confidence: 99%